Intergovermental Cooperation Initiative on Sustainable Transportation Management in Jabodetabek - Chotimah, Hidayat Chusnul (Jurnal Bina Praja, 2016)
The main issues in Jabodetabek concerning the management of transportation are related to the increased use of private vehicles and the decreased use of public transportation, overcrowding daily traffic in Jabodetabek, the high congestion followed by insecurity in traffic, environmental pollution, uncontrolled growth of and underdeveloped infrastructure, and irregularities in land use. To overcome these problems, sustainable transportation management becomes very important in which the government should be able to cope with environmental, economic and social factors under the decision making related to transportation in Jabodetabek. Therefore, through interactive planning, this study will examine intergovernmental cooperation initiatives on sustainable transportation management in Jabodetabek. This study uses qualitative and descriptive method through literature study and existing statistics as the resources to apply the interactive planning approach. The result shows that there are found a number of problems and gaps in the management of transportation in Jabodetabek that needs to be reduced because it has the same scope of other gaps. From these problems can be made further action programs and policies in accordance with the resources owned, and then, the design of implementation made and controlled whether in accordance with the purpose or not. Thus, sustainable transportation management in the Jabodetabek needs to be done jointly in an institutional or policyframework involving governments Jabodetabekpunjur, BKSP Jabodetabekpunjur, and the private sector.